2019
DOI: 10.24940/theijbm/2019/v7/i6/bm1906-039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coping Strategies for Work-Life Conflict: A Focus on Selected Deposit Money Banks in Aba, Abia State Nigeria

Abstract: Introduction Life ordinarily is lived in multiple but related domains such as work, family, recreation, religion and leisure. However, of these domains, work and life (family) are seen as the dominant and most active domains of an adult. As noted by Grywacz and Bass (2003), how work and family intersect in a person's life, or rather how they fit, have been reported to have important ramifications for individuals and families. In other words, giving more attention to one domain will affect the others and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Data analysis also supported Hypothesis 2: social competence positively correlates with employee psychological well-being, confirmed in previous studies(Gómez-López et al, 2022). Social competencies plausibly positively relate to employee psychological well-being because it is a composite of social skills such as social adaptability, emotional intelligence, and social intelligence that have the potential to improve interpersonal relationships(Holopainen et al, 2012;Onyemaechi & Ikpeazu, 2020). People in cordial relationships with others are likely to express joy and happiness, fundamental components of psychological well-being.Hypothesis 3 on moderation was confirmed.…”
supporting
confidence: 74%
“…Data analysis also supported Hypothesis 2: social competence positively correlates with employee psychological well-being, confirmed in previous studies(Gómez-López et al, 2022). Social competencies plausibly positively relate to employee psychological well-being because it is a composite of social skills such as social adaptability, emotional intelligence, and social intelligence that have the potential to improve interpersonal relationships(Holopainen et al, 2012;Onyemaechi & Ikpeazu, 2020). People in cordial relationships with others are likely to express joy and happiness, fundamental components of psychological well-being.Hypothesis 3 on moderation was confirmed.…”
supporting
confidence: 74%
“…It is a technique for upholding services, improving productivity and establishing trust by providing psychological and educational assistance (Reddy, 2017). Studies such as Onyemaechi and Ikpeazu (2019), Nurul (2014) and Richard et al (2015) posited that peer review mentorship enhances the relationships among co-workers and improves service delivery and organizational performance. Similarly, Piraeus (2018) found that peer review mentoring enhances the working relationship and improves workers' effectiveness.…”
Section: Peer Review Mentorship and Quality Service Deliverymentioning
confidence: 99%
“…Against this backdrop, this study seeks to examine the effect of mentoring on quality service delivery in Federal Universities in Nigeria. Mentoring can be acquired through supervision (Eby & Allen, 2012;Ekechukwu & Horsfall (2015), career development (Braer & Simmons, 2018;Jeevan & Poonam, 2015), peer review (Onyemaechi & Ikpeazu, 2019;Nurul, 2014;Richard et al, 2015) as well as role modelling (Daniel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mentorship is a human resources technique that uses a targeted dyadic connection to help individuals enhance their professional skills and advance their careers. This approach entails pairing novice people with experienced ones for the latter to convey knowledge, confidence, abilities, and other advantages to the less experienced person (29). The quality of mentorship for a new employee significantly contributes to their socialization and learning, and it can be highly effective in improving work attitudes and employee engagement (20).…”
Section: Mentorshipmentioning
confidence: 99%